Aristolochic acid and its derivatives as inhibitors of snake venom L-amino acid oxidase. (November 2017) - Bhattacharjee, Payel; Bera, Indrani; Chakraborty, Subhamoy; Ghoshal, Nanda; Bhattacharyya, Debasish
Abstract: Snake venomL -amino acid oxidase (LAAO) exerts toxicity by inducing hemorrhage, pneumorrhagia, pulmonary edema, cardiac edema, liver cell necrosis etc . Being well conserved, inhibitors of the enzyme may be synthesized using the template of the substrate, substrate binding site and features of the catalytic site of the enzyme. Previous findings showed that aristolochic acid (AA), a major constituent of Aristolochia indica, inhibits Russell's viper venom LAAO enzyme activity since, AA interacts with DNA and causes genotoxicity, derivatives of this compound were synthesized by replacing the nitro group to reduce toxicity while retaining the inhibitory potency. The interactions of AA and its derivatives with LAAO were followed by inhibition kinetics and surface plasmon resonance. Similar interactions with DNA were followed by absorption spectroscopy and atomic force microscopy. LAAO-induced cytotoxicity was evaluated by generation of reactive oxygen species (ROS), cell viability assays, confocal and epifluorescence microscopy. The hydroxyl (AA-OH) and chloro (AA-Cl) derivatives acted as inhibitors of LAAO but did not interact with DNA. The derivatives significantly reduced LAAO-induced ROS generation and cytotoxicity in human embryonic kidney (HEK 293) and hepatoma (HepG2) cell lines. Confocal images indicated that AA, AA-OH and AA-Cl interfered with the binding of LAAO to the cell membrane. AA-OH and AA-Cl significantly inhibited LAAO activity and reduced LAAO-induced cytotoxicity. Highlights: Aristolochic acid (AA) inhibits activity of snake venomL amino acid oxidase. Since AA is genotoxic, its hydroxyl and chloro derivatives were synthesized. The derivatives lack DNA binding ability. These derivatives are nontoxic but inhibitors ofL amino acid oxidase.